Fetal macrophages - Martin, Paul (Henry Stewart Talks, 2012)
The history of studying of macrophages, The benefits of the various model organisms for studying macrophages; zebrafish, mice, drosophila and C. elegans, The primary function of embryonic macrophages is to clear away apoptotic cell debris